Cross-Bridge Free Vascularized Fibular Graft for Reconstruction of Extensive Traumatic Tibial Defects - El-Gammal, Tarek Abdalla; El-Sayed, Amr; Kotb, Mohamed Mostafa; Saleh, Waleed Riad; Ragheb, Yasser Farouk; Morsy, Mohamed Mohamed; El-Gammal, Yousif Tarek; Saad, Mahmoud Mohammed; Refai, Omar Ahmed (Journal of Reconstructive Microsurgery Open, 2025)
Background The cross-bridge free flap technique has been described for salvage of cases of traumatic lower limb defects when adequate recipient vessels in the same limb are lacking. While previous accounts mainly focused on utilizing muscle, myocutaneous, or perforator skin flaps, this study presents a series of cross-bridge free vascularized fibular transfer for reconstruction of traumatic tibial defects with extensive soft tissue loss.Methods The study included 22 cases with an average age at surgery of 24 ± 8 years and an average tibial bone defect of 14.2 ± 3.3 cm. In this technique, the fibula was inset into the tibial defect and vascularization was performed using the posterior tibial artery of the contralateral leg through a radial forearm flap. The two legs were coimmobilized using Hoffmann external fixator and subsequently separated after 6 weeks.Results All flaps survived. Follow-up averaged 44.4 months. Union occurred in all cases within an average of 4.5 ± 1.9 months and Full weight-bearing was achieved at an average of 9.0 ± 2 months. Stress fractures occurred in eight patients (36.3%) after an average of 12 months. Mean graft hypertrophy at the final follow-up was 67.6%. Six patients showed an average limb length discrepancy of 4.2 cm. Two patients required corrective osteotomy, one ankle fusion, and another Achilles tendon lengthening. Functionally, 20 patients were able to walk without crutches.Conclusion The cross-bridge free vascularized fibular graft is a viable option for reconstruction of complex and extensive tibial defects when no other reconstructive options are available.
Keywords: cross-bridge; vascularized fibula; tibial defects